Hearing the Sound of the Wave: What Impedes One’s Ability to Foresee Innovations? - Vladimir Milovidov (Foresight and STI Governance, 2018)
This paper offers a broad view on foreseeing innovation, which is not limited solely to early detection at the micro level. The author defines innovations as ongoing processes of changes in the various fields of social and economic life, which result from human creative activity. Noting that innovation is an uncertain, relatively chaotic, and disordered process characterized by inherent risks, the author aims to define the most general and universal barriers impeding one’s ability to recognize the signs of future innovation and to anticipate their consequences. Considering examples of «disruptive innovation» in the technological, social, political, and economic spheres of life, the author sees these innovations as arising from certain condition and events, not as simple random occurences. Most of them are effects of particular causes. However, these causes are often hidden within events that are difficult to observe and phenomena encapsulated in weak signals. The inability to detect and recognize such pre-emerging warnings of upcoming innovations may be attributed to the massive amount of information signals and noise flooding today’s world. This problem is excaerbated by the lack of knowledge, techniques, and experience for dealing with huge amounts of information, the lack of the required skills, and, finally, by human cognitive biases. Faced with this deluge of misinformation, any person can eventually be misled and make mistakes. This paper posits that, in order to mitigate such risks, an individual must avoid the three cognitive biases: the symmetry of delusions, aggressive neglect, and the curse of knowledge. These cognitive biases are the barriers to foreseeing innovation.